2018
DOI: 10.1097/aln.0000000000002274
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Lumbar Facet Joint Blocks and Predictive Value before Radiofrequency Denervation

Abstract: What We Already Know about This Topic What This Article Tells Us That Is New Background With facet interventions under scrutiny, the authors’ objectives were to determine the effectiveness of different lumbar facet blocks and their ability to predict radiofrequency ablation outcomes. Methods A total of 229 participants were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 49 publications
1
78
0
3
Order By: Relevance
“…78 Despite consistent evidence of only small effect sizes for conservative treatments (including PT) in chronic LBP, 79 80 proponents still recommend conservative care trials due to their relatively lower costs and risks. This position appears to be supported by interventional pain researchers since the inclusion criteria within prospective studies of facet joint interventions usually, 18 19 81–83 but not always, 84 85 include a preceding trial of conservative treatment. Yet, there is no existing evidence that demonstrates the appropriate timing or optimal duration of conservative treatments for chronic LBP.…”
Section: Question 3: Should Physical Therapy And/or Prior Conservativmentioning
confidence: 97%
See 3 more Smart Citations
“…78 Despite consistent evidence of only small effect sizes for conservative treatments (including PT) in chronic LBP, 79 80 proponents still recommend conservative care trials due to their relatively lower costs and risks. This position appears to be supported by interventional pain researchers since the inclusion criteria within prospective studies of facet joint interventions usually, 18 19 81–83 but not always, 84 85 include a preceding trial of conservative treatment. Yet, there is no existing evidence that demonstrates the appropriate timing or optimal duration of conservative treatments for chronic LBP.…”
Section: Question 3: Should Physical Therapy And/or Prior Conservativmentioning
confidence: 97%
“…MBB remained a significant predictor for positive treatment response even when controlling for confounding factors. In the subsequent randomized, three-arm FACTS study by Cohen et al , 18 the authors found a false-positive rate of 30% when defined as significant pain relief following a lumbar MBB with saline. The proportions of positive responders to RFA in the IA and medial block diagnostic groups were 51% and 56%, respectively.…”
Section: Question 5: Are Facet Blocks ‘Diagnostic’ ‘Prognostic’ or Bmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still a very controversial procedure in terms of efficiency. Some studies showed its superiority to placebo or conservative treatment where others were not conclusive [4][5][6]. We consider it as a safe, minimally invasive, inexpensive procedure.…”
Section: Introductionmentioning
confidence: 91%